Ethnomedicinal uses, Phytochemistry and Pharmacological Aspects of the Genus Berberis Linn: A Comprehensive Review - Mohi-ud-din, Roohi; Mir, Reyaz H.; Mir, Prince Ahad; Farooq, Saeema; Raza, Syed Naiem; Raja, Weekar Younis; Masoodi, Mubashir Hussain; Singh, Inder Pal; Bhat, Zulfiqar Ali (Combinatorial Chemistry & High Throughput Screening, 2021)
Background: Genus Berberis (family Berberidaceae), which contains about 650 species and 17 genera worldwide, has been used in folklore and various traditional medicine systems. Berberis Linn. is the most established group among genera with around 450-500 species across the world. This comprehensive review will not only help researchers for further evaluation but also provide substantial information for future exploitation of species to develop novel herbal formulations. Objective: The present review is focussed to summarize and collect the updated review of information of Berberis species reported to date regarding their ethnomedicinal information, chemical constituents, traditional/folklore use, and reported pharmacological activities on more than 40 species of Berberis. Conclusion: A comprehensive survey of the literature reveals that various species of the genus possess various phytoconstituents mainly alkaloids, flavonoid based compounds isolated from different parts of a plant with a wide range of pharmacological activities. So far, many pharmacological activities like anti-cancer, anti-hyperlipidemic, hepatoprotective, immunomodulatory, antiinflammatory both in vitro and in vivo and clinical study of different extracts/isolated compounds of different species of Berberis have been reported, proving their importance as a medicinal plant and claiming their traditional use.
Keywords: phytochemistry